2022
DOI: 10.3758/s13423-022-02129-6
|View full text |Cite
|
Sign up to set email alerts
|

What the study of spinal cord injured patients can tell us about the significance of the body in cognition

Abstract: Although in the last three decades philosophers, psychologists and neuroscientists have produced numerous studies on human cognition, the debate concerning its nature is still heated and current views on the subject are somewhat antithetical. On the one hand, there are those who adhere to a view implying ‘disembodiment’ which suggests that cognition is based entirely on symbolic processes. On the other hand, a family of theories referred to as the Embodied Cognition Theories (ECT) postulate that creating and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 149 publications
0
15
0
Order By: Relevance
“…Several studies have shown that chronic deafferentation (loss of sensory input) and de‐efferentation (loss of motor output) substantially change the functional organization of the cortical somatotopy both in animals (Aguilar et al, 2010; Brown & Martinez, 2019; Filipp et al, 2019; Kambi et al, 2014) and humans (Curt et al, 2002; Filipp et al, 2019; Freund et al, 2013; Henderson et al, 2011; Leemhuis et al, 2022). Consistently, behavioural studies in patients affected by SCI revealed the presence of body‐part‐specific deficits in action and body form recognition (Pernigo et al, 2012), in body ownership (Lenggenhager et al, 2012), in motor imagery (Scandola et al, 2017) and in the perception of biological motion (Arrighi et al, 2011; see Moro et al, 2022, 2023 for recent reviews). It is worth noting, however, that significant effects of chronic deafferentation and deefferentation on discrimination of action related sounds perception is not always reported (e.g., Pazzaglia et al, 2018; Vannuscorps & Caramazza, 2016).…”
Section: Introductionmentioning
confidence: 85%
“…Several studies have shown that chronic deafferentation (loss of sensory input) and de‐efferentation (loss of motor output) substantially change the functional organization of the cortical somatotopy both in animals (Aguilar et al, 2010; Brown & Martinez, 2019; Filipp et al, 2019; Kambi et al, 2014) and humans (Curt et al, 2002; Filipp et al, 2019; Freund et al, 2013; Henderson et al, 2011; Leemhuis et al, 2022). Consistently, behavioural studies in patients affected by SCI revealed the presence of body‐part‐specific deficits in action and body form recognition (Pernigo et al, 2012), in body ownership (Lenggenhager et al, 2012), in motor imagery (Scandola et al, 2017) and in the perception of biological motion (Arrighi et al, 2011; see Moro et al, 2022, 2023 for recent reviews). It is worth noting, however, that significant effects of chronic deafferentation and deefferentation on discrimination of action related sounds perception is not always reported (e.g., Pazzaglia et al, 2018; Vannuscorps & Caramazza, 2016).…”
Section: Introductionmentioning
confidence: 85%
“…For example, SCI is associated with changes in action representation (Arrighi et al, 2011;Ionta et al, 2016;Pernigo et al, 2012;Scandola et al, 2016) and body representation (Pernigo et al, 2012;Scandola, Aglioti, Pozeg, et al, 2017;Scandola et al, 2014Scandola et al, , 2019 which are specific to the paralyzed and anesthetized body parts. Spatial functions also change in paraplegic individuals, with a reduction in the representation of the space around the feet but not around the hands (Moro et al, 2022;Scandola et al, 2016Scandola et al, , 2020.…”
Section: Sensorimotor and Affective Components Of Empathic Responses ...mentioning
confidence: 99%
“…In sum, these mental body representation deficits hinder functional recovery because the brain does not recognize the body's spatial location to guide movements. [4][5][6][12][13][14]18 Adults who have SCI-related neuropathic pain often have an altered perception related to the size and dimension of the painful and/or sensorimotor-impaired body parts, which justifies the use of CMR to treat neuropathic pain. They also have an altered perception of body weight, pressure, or touch in those body regions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Increasing evidence shows that adults with SCI with motor and sensory impairments also experience body awareness deficits. [4][5][6][7][8][9][10][11][12][13][14][15] Body awareness refers to an attentional focus on and awareness of internal body sensations, including whole-body awareness as well as awareness of body parts in relation to each other, and how they are positioned and move in space. 16,17 These motor and sensory impairments, and particularly the loss of awareness of where the limbs are in space, 18 greatly compromise function and mobility.…”
Section: Introductionmentioning
confidence: 99%